Exploring Technology, Role, and Components of Computational Thinking in Mathematics Learning: A Systematic Literature Review - Andriatna, Riki; Turmudi, Turmudi (JTAM (Jurnal Teori dan Aplikasi Matematika), 2025)
Computational thinking as a 21st century skill has attracted the attention of researchers, including in mathematics education. This research identifies the use of technology, the role and components of computational thinking in mathematics learning. This study uses a sysematic literature review with procedure consisting of planning the review, conducting the review, and reporting the review. The articles used came from the Scopus database in the 2010-2024 publication time range. Based on the PRISMA protocol involving criteria such as type of publication, language, field of study, publication stage, and accessibility to the article, 11 articles were obtained with the most research conducted in Spain. The research conducted involved many students and teachers as the object of research, including pre-service teachers. The reviewed studies also revealed that most of the computational thinking research used qualitative methods where the role of computational thinking in the research was mostly as a process or activity or tools used in learning, either using technological devices or in the form of unplugged activites. In addition, the results of the review of selected articles also reveal that the components of decomposition, pattern recognition, abstraction, and algorithm are still dominating as the main components studied in computational thinking.